Analisis Swot Dalam Rangka Meningkatkan Penjualan Pada Studio Isoarchives Kecamatan Dampit Kabupaten Malang - Nugroho, Rendra Cahyo; Widarko, Agus; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze SWOT in order to increase sales at Studio Isoarchives. The location of this research was carried out on employees of Studio Isoarchives located in Dampit District, Malang Regency. This research is a qualitative research. This research is research carried out by obtaining data sourced from the research location relating to the research title. This research uses descriptive qualitative analysis because the research carried out requires information using observation data, documentation studies, and interviews as well as distributing questionnaires which then aims to obtain data on the company's external and internal factors which then become the basis for research. Objects are informants or sources who are the source of research data. The subjects are the owners and employees of Studio Isoarchive. The data was analyzed using the data analysis technique used in this research is SWOT analysis. Based on the results of data analysis, the research results show that SWOT strategy analysis can increase sales at Studio Isoarchives. SWOT strategy analysis helps companies to find out the company's strengths, weaknesses, opportunities and threats. This is used to develop the right strategy in an effort to increase sales volume. To optimize the implementation of SWOT strategy analysis properly and based on the results of researchers, there is a need to increase the application of SWOT strategy analysis so that sales volume can be increased optimally, especially in analyzing existing opportunities, promotion needs to be encouraged again by advertising products and strengthening business networks, and there needs to be increased market expansion and companies need to innovate on Isoarchives studio services. Keywords: Increased Sales, and SWOT Analysis.